Microgreens: Alternatif Konsumsi Sayur Bergizi dan Praktik Budidaya Ramah Lingkungan di Lingkungan Rumah Tangga: Review - Suminar, Ratna; Ayuningtyas Harini, Nyang Vania; Sapta Andrialin, Gian (Universitas Muhammadiyah Kotabumi, 2025)
The low consumption of vegetables in Indonesia and the increasing need for environmentally friendly urban farming solutions are important challenges in realizing a healthy and sustainable diet. Microgreens present an innovative alternative that is not only highly nutritious, but also easy to cultivate at various scales, including in the household environment. This study aims to analyze the nutritional content and bioactive compounds in various types of microgreens and evaluate their health benefits and potential as a functional food source. In addition, this study also illustrates the ease of cultivating microgreens as part of sustainable urban agriculture. The method used was a literature study with a systematic literature review approach of scientific sources published in 2016-2024, such as accredited journals, reference books, and research reports. The results showed that microgreens contain high levels of vitamins, minerals and antioxidants, and have a short harvest period and minimal land requirements. The use of technologies such as LED lighting, suitable growing media and high-quality seeds greatly influence the success of cultivation. Despite challenges in distribution and product durability, microgreens hold promise as a functional food that supports food security, nutrition education and healthy lifestyles in urban areas.